Ethnomedicinal plants in Champadevi rural municipality, Okhaldhunga district, Nepal - Deepa Karki; Dipak Khadka; Ripu Mardhan Kunwar; Prakash Chandra Aryal; Hem Raj Paudel; Sijar Bhatta; Shi Shi (BMC, 2023)
Abstract Background Okhaldhunga is a hilly district with fragile socioeconomic conditions, limited access to health care, social stigma, and poor resource management, where most people rely on medicinal plants for primary health care. The use of medicinal plants for primary health care varies with socioeconomic attributes. Following the intra-cultural analysis, we documented and tested the hypothesis that use of medicinal plants in Champadevi, Okhaldhunga, Nepal, depends on socioeconomic variables. Methods We interviewed 224 respondents, 53.12% female and 46.88% male, including 31 Brahmin, 157 Chhetri, 13 Dalit, and 23 Janajati, and conducted three focused group discussions and seven key informant interviews to record the ethnomedicinal plants used in Champadevi rural municipality, Okhaldhunga District. The relative frequency of citation (RFC) was computed to know the importance of the species. A generalized linear model (GLM) was used to see the relationship between medicinal plants reported with the sociocultural variables, which include age, gender, occupation, education, ethnicity, and religion. Results We documented 149 medicinal plants, including 69 herbs, 22 shrubs, nine climbers, 48 trees, and one parasitic plant, belonging to 68 families and 130 genera, and used to treat 48 distinct diseases and ailments. Plant parts, leaf, and digestive disorders were frequently treated during healing. Curcuma angustifolia was the most cited species with RFC 0.9554. The respondents' knowledge of medicinal plant use varied significantly with age (p = 0.0001) and occupation (p = 0.003). Changes in land use, population decline of medicinal plant species, and unsustainable harvesting practices constituted the local threats to medicinal plants and associated knowledge. Elders died without passing on their knowledge to the younger generations during sociocultural transformation, and youth disinterest coupled with the free availability of allopathic medicine led to knowledge erosion. Conclusions The use of medicinal plants in Champadevi, Okhaldhunga, was significantly depended on two socioeconomic variables age and occupation. Ethnomedicinal plants are essential in the primary healthcare system in Nepal; however, their availability and practices are declining. Thus, plans regulating land use change and human migration, acknowledging traditional healthcare practices, and raising awareness of the significance of traditional medical practices as complementary healthcare practices should be strengthened.